Severe epidermolysis bullosa/Kindler syndrome‐like phenotype of an autoinflammatory syndrome in a child. (1st June 2021) - Mahajan, R.; Bishnoi, A.; Manjunath, S.; Vignesh, P.; Suri, D.; Gopal, M.; Chatterjee, D.; Jamwal, M.; De, D.; Das, R.; Handa, S.; Kubba, A.; et al.
Summary: A 5‐year‐old boy presented with generalized cutaneous erosions, severe scarring, depigmentation and contractures affecting major joints. The lesions had initially affected his ears, nose, feet, and the genital and ocular mucosa, leading to significant depigmentation, scarring, contractures and mutilation. The whole of the trunk and limbs were involved at the time of presentation, with the exception of some islands of spared skin on the proximal thighs, legs, nipples and external genitalia. Electron microscopy revealed a split in the sublamina densa with the absence of anchoring fibrils, suggestive of dystrophic epidermolysis bullosa (EB). Immunofluorescence antigen mapping demonstrated a broad reticulate pattern of staining with collagen IV, VII, and laminin 332 in the floor of the blister, suggestive of Kindler syndrome. Next‐generation sequencing revealed a de novo heterozygous missense mutation (a variant of unknown significance) in exon 22 of the phospholipase‐C gamma 2 gene ( PLCG2 ), which resulted in a substitution of serine by asparagine at codon 798 (p.Asp798Ser), a result that was validated using Sanger sequencing. The child was diagnosed with PLCG2 ‐associated antibody deficiency and immune dysregulation (PLAID)/autoinflammation and PLCG2 ‐associated antibody deficiency and immune dysregulation (APLAID) syndrome. The cutaneous and corneal erosions, inflammation and scarring of this magnitude, and the eventual result of death have not been described previously for the PLAID/APLAID spectrum previously. In conclusion, this was an unusual acquired autoinflammatory severe EB‐like disease that may be associated with de novo PLCG2 mutation. Abstract : Click here for the corresponding questions to this CME article.